Mobile Application Purchase: Comparison of Utilitarian Features between Users and Non-users - Emad Rahmanian; Hassan Abomolouki (Department of Communications, Universitas Islam Indonesia, 2021)
Abstract.This study aims to understand how utilitarian features of a mobile application moderate purchase motivations and intentions among users and non-users. Taking a case of cinema ticket purchase in the Iranian context, this study has collected empirical data through a questionnaire from 240 respondents. Multiple regression analysis was used to analyze data. Motivational variables were grouped into four groups: functional motivations, convenience-based functional motivations, product motivations, and service motivations. In addition, the gender issue of the consumer was also considered. This study finds that such motivational factors significantly affect consumers’ motivations, both male and female consumers. Analysis on gender shows no significant differences among male and female consumers. Therefore, these factors should be considered in formulating marketing communication strategy and media management, especially for non-users. Further research should consider other motivational factors, such as hedonic motivations, attitude, and situational factors, to understand consumer behaviors comprehensively.Keywords: marketing communication, mobile application, mobile purchase, utilitarian features, mobile marketing, cinema ticket.